Profile of newborns hospitalized in a kangaroo ward of a public maternity - Isabel Cristina da Silva Santos, Mércia Lisieux Vaz da Costa Mascarenhas, Ingrid Martins Leite Lúcio, Rossana Teotônio de Farias Moreira (Revista de Enfermagem da UFPI, 2020)
DOI: https://doi.org/10.26694/reufpi.v2i1.747